Elements of Palliative Care in the Last 6 Months of Life: Frequency, Predictors, and Timing - Ernecoff, Natalie C. (J Gen Intern Med, 2019)
IMPORTANCE: Persons living with serious illness often need skilled symptom management, communication, and spiritual support. Palliative care addresses these needs and may be delivered by either specialists or clinicians trained in other fields. It is important to understand core elements of palliative care to best provide patient-centered care. OBJECTIVE: To describe frequency, predictors, and timing of core elements of palliative care during the last 6 months of life. DESIGN: Retrospective chart review. SETTING: Inpatient academic medical center. PARTICIPANTS: Decedents with cancer, dementia, or chronic kidney disease (CKD) admitted during the 6 months preceding death. EXPOSURES: We identified receipt and timing of core elements of palliative care: pain and symptom management, goals of care, spiritual care; and specialty palliative care utilization; hospital encounters; demographics; and comorbid diagnoses. We ran Poisson regression models to assess whether diagnosis or hospital encounters were associated with core elements of palliative care. RESULTS: Among 402 decedents, the mean (SD) number of appropriately screened and treated symptoms was 2.9 (1.7)/10. Among 76.1% with documented goals of care, 58.0% had a primary goal of comfort; 55.0% had documented spiritual care. In multivariable models, compared with decedents with cancer, those with dementia or CKD were less likely to have pain and symptom management (respectively, 31% (incidence rate ratio [IRR], 0.69; 95% CI, 0.56–0.85) and 17% (IRR, 0.83; CI, 0.71–0.97)). There was a median of 3 days (IQR, 0–173) between transition to a goal of comfort and death, and a median of 12 days (IQR, 5–47) between hospice referral and death. CONCLUSIONS AND RELEVANCE: Although a high proportion of patients received elements of palliative care, transitions to a goal of comfort or hospice happened very near death. Palliative care delivery can be improved by systematizing existing mechanisms, including prompts for earlier goals-of-care discussion, symptom screening, and spiritual care, and by building collaboration between primary and specialty palliative care services.